Clark, John (2024): The Green Children of Woolpit. Chronicles, Fairies and Facts in Medieval England, Exeter, University of Exeter Press (Exeter New Approaches to Legend, Folklore and Popular Belief), 260 pp. - Guillén Ortiz, Adriana (Boletín de Literatura Oral, 2025)
Reseña